Effects of low-level laser therapy on the modulation of tissue temperature and hyperalgesia following a partial Achilles tendon injury in rats. (3rd October 2017) - Gomes, Cid André Fidelis de Paula; Dibai-Filho, Almir Vieira; Pallotta, Rodney Capp; da Silva, Evela Aparecida Pereira; Marques, Anna Cristina de Farias; Marcos, Rodrigo Labat; de Carvalho, Paulo de Tarso Camillo
ABSTRACT: The aim of the present study was to evaluate the effects of low-level laser therapy (LLLT) on the modulation of tissue temperature and hyperalgesia following a partial injury to the Achilles tendon in rats. Forty-five rats were randomly divided into three groups: a control group, a group treated with LLLT at a dose of 1.4 J (808 nm, 50 mW, 1.4 J), and a group treated with LLLT at a dose of 2.1 J (808 nm, 50 mW, 2.1 J). LLLT was administered to a single point immediately following the partial injury of the Achilles tendon. Tissue temperature and hyperalgesia were evaluated 6, 24, and 48 hours following the injury. Thus, a significant group-versus-time interaction was found for tissue temperature ( F = 4.097, p = 0.001) and hyperalgesia ( F = 106.605, p < 0.001), with a greater reduction in theses outcomes in the group that received LLLT at a dose of 2.1 J evaluated 48 hours after the injury. Therefore, LLLT at a wavelength of 808 nm and dose of 2.1 J administered immediately following a partial injury to the Achilles tendon led to a reduction in tissue temperature and hyperalgesia at the injury site in rats, especially 48 hours after injury.